Small Entreprises Fundamental Problems in Bali Province - Pardita, Dewa Putu Yudi; Laksmi, Putu Ayu Sita; Putra, I Putu Iwan Pramana; Pramana, Made Surya (Budapest International Research and Critics University, 2021)
The problems faced by small businesses are closely related to a companion or facilitator in assisting. The lack of guidance makes it difficult for small businesses to develop. Based on the results of coaching and monitoring of 30 profiles of small business groups in Bali Province, there are several types of obstacles or problems that are often complained of by small business actors in the industrial sector in Bali Province, namely the low quality of human resources and the lack of entrepreneurial knowledge and competence resulting in everyday business and labor productivity. This can also be seen in the inability of business actors in terms of business management, especially in terms of recording/bookkeeping procedures. Many business actors also do not have a transparent legal entity, lack product innovation. Small businesses are considered to lack still knowledge of technology, management, information, and markets. Observing the problems faced by small businesses in the future, it is necessary to create a conducive climate, among others, by seeking peace and security in business and simplifying business licensing procedures, tax breaks, and so on. Government capital assistance needs to expand special credit with conditions that are not burdensome for small businesses to help increase their capital through the formal financial services sector, the informal financial services sector, guarantee schemes, and leasing venture capital funds. The government needs to improve training for small business actors in entrepreneurship, management, administration, and knowledge and skills in business development. Besides that, it is also necessary to apply the training results in the field to practice theory through the development of pilot partnerships.